Transformation of Al-Qur'an Interpretation in the Digital Era: A Comparative Analysis Study of the Content of the Altafsir.com Website with the Al-Qur'an Al-Hadi Website - Amalia Naim Afifah; Ahmad Nurrohim; Kharis Nugroho; Yeti Dahliana; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to discuss the study of online interpretations on the Altafsir.com website and Al-Qur'an Al-Hadi by examining the content on the two websites, in terms of methods, approaches and patterns used on the two websites. This study uses a library research type with qualitative descriptive analysis that processes data, analyzes data and includes the validity of the interpretation studies on the two websites. The author concludes that these two websites have different characteristics. The website uses the interpretation method per verse, and per letter, while Al-Qur'an Al-Hadi uses the method per verse and per theme. The approach used by Altafsir.com is the interpretation of classical and modern scholars, while Al-Qur'an Al-Hadi uses theimaudhu'i interpretation approach or thematiciinterpretation in presenting theiinterpretationiof theiverses of theiQur'an. combining textual and contextual approaches. In terms of interpretation style, Altafsir.com uses the adab ijtima'i, Fiqhi and lughawi style while Al-Qur'an Al-Hadi offers three interpretation options: Ibn Katsir, Tafsir Tahlili and Tafsir and Jalalayn. Both websites are declared valid because they are in accordance with threeitheories of truth, namelyithe theory of coherence,icorrespondence, and pragmatics.